Il rapporto medico-paziente in psichiatria e psicoterapia: il concetto di influenzamento nel rapporto interumano - Anzilotti, Carlo (Il sogno della farfalla, 2014)
The article reconstructs the origins of the concept of countertransference, when it wasn’t yet defined as such. To this end the history of hypnosis is retold, having its antecedents in Mesmer’s animal magnetism, when it finally turns into “psychotherapy” at the end of the 1800s, thus expressing a therapeutic intention on the part of the doctors. Magnetism, hypnosis and psychotherapy are all practices based on suggestion, that is the possibility of therapeutically influencing the mind of another human being to cure him of mental disorders. At the start of the 19th century the historical progress of such practices suddenly stops, and psychotherapy is relegated to a rather marginal role in relation to Freudian psychoanalysis.